Building Brand Relationship Through Millennial Generation Behaviors: Marketing Strategy on Instagram - Tantra, Geralda Carnelian (VCD: Journal of Visual Communication Design, 2021)
The theme of this research is the preparation of a marketing strategy in social media by considering the market and considerations of the aforementioned social media platforms. This study aims at the behavior of the intended target market and the development of suitable methods for that market to improve the performance of content development on Instagram social media. This research is based on the theory that has been put forward by marketing experts and business innovation which can be applied simply in the marketing activities held. The close relationship between the brand and the target market will show the role of communication through targeted marketing activities, especially in Indonesia. Keywords: Brand, Target Market, Instagram, Communication, Marketing Strategy.